Implicit Grammatical Gender Representation in Italian Children with Autism without Intellectual/Language Disorder - Caterina Artuso; Carmen Belacchi (MDPI AG, 2023)
Grammatical language development in individuals with autism (without intellectual/language impairment) is mostly qualitatively comparable to language development in typically developing children of the same age. The majority of tasks used to study grammatical development require explicit performance (use of verbal language). Here, we administered an implicit categorization task (by biological sex) to understand which markers children use to implicitly infer grammatical gender representation in Italian (a gendered language where grammatical gender can be inferred via a determiner and/or word ending). Participants were asked to categorize photos of animals, relying on the names that differed in regard to the grammatical markers involved (i.e., lexical semantic, phonological, syntactic or phonological + syntactic). Children with autism displayed the same patterns observed in typically developing children: the lexical-semantic marker was categorized more accurately, followed in decreasing order by the phonological-syntactic marker and the phonological marker. The syntactic marker was the most difficult to categorize for both groups. In addition, children with autism showed an advantage in grammatical gender representation when using formal/grammatical markers than when using lexical/semantic markers. Such an implicit assessment allows for the investigation of more nuanced linguistic representations other than those expressed by traditional assessments.